To complete the statements for the given quadratic equation \( x^2 + 4x + 3 = 0 \):
- The value of \( a \) is 1 (the coefficient of \( x^2 \)).
- The value of \( b \) is 4 (the coefficient of \( x \)).
- The value of \( c \) is 3 (the constant term).
To find one solution to the equation, we can factor it, or use the quadratic formula.
The equation can be factored as:
\[ (x + 1)(x + 3) = 0 \]
Setting each factor to zero gives us the solutions:
- \( x + 1 = 0 \) → \( x = -1 \)
- \( x + 3 = 0 \) → \( x = -3 \)
Thus, one solution to the equation is -1 (or you could also state -3).